Quinoxalin-2-yl m-tolyl ether. - Hassan, N.D.; Tajuddin, H.A.; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2008)
The dihedral angle between the two aromatic ring systems in the title compound, C(15)H(12)N(2)O, is 79.4 (1)°. The angle at the O atom is widened to 116.93 (9)°.